Ultrasound of the Optic Nerve Does Not Appear to Be a Consistently Reliable or Generalizable Method to Monitor Changes in Intracranial Pressure. (May 2022) - Butts, Christine; Wilson, Jason; Lasseigne, Lindsay; Oral, Evrim; Kaban, Nicole
Objective: Invasive intracranial pressure (ICP) monitoring is the gold standard, but is not always readily accessible or practical. Ultrasound of the optic nerve sheath diameter (ONSD) has been proposed for detecting both elevation and change in the ICP. Our study is a prospective observational trial that seeks to determine if ultrasound can be reliably used to identify changes in ICP with naturally occurring variations in patient care. Methods: A convenience sample of patients with invasive ICP monitoring were enrolled. Patients were identified prior to interventions that were suspected to cause a change in ICP. Measurement of ICP and ONSD was obtained prior to the intervention, with repeated measurements of both variables obtained immediately following the intervention. Results: 36 total patients were enrolled. There was a positive correlation between the ICP and the right ONSD (r = 0.255, P = 0.0003) and the ICP and the left ONSD (r = 0.274, P < 0.0001). There was no statistically significant relationship between the change in either the ICP and the right ONSD (r −0.2 P = 0.282) or left ONSD (r 0.05 P = 0.805). The location of the lesion in the brain appears to significantly affect discordance between the ONSD and the ICP. Conclusions: Ultrasound of the ONSD has shown promise as both a marker of elevated ICP and as a method to identify changes in pressure. Although the size of the ONSD and the measurement of ICP were correlated in our study, the ability to follow changes in ICP was not statistically significant. This indicates that use of ultrasound to track changes in ICP cannot be generalized and may be limited to specific circumstances. The location of the intracranial pathology appears to be a significant factor in discordance between the ICP and ONS diameter.